Clonal evolution and resistance to EGFR blockade in the blood of colorectal cancer patients - Siravegna, Giulia; Mussolin, Benedetta; Buscarino, Michela; Corti, Giorgio; Cassingena, Andrea; Crisafulli, Giovanni; Ponzetti, Agostino; Cremolini, Chiara; Amatu, Alessio; Lauricella, Calogero; Lamba, Simona; Hobor, Sebastijan; et al. (Nature medicine, 2015)
By monitoring ctDNA, the authors reveal the dynamic adaption of clonal populations in colorectal cancer patients treated with anti-EGFR therapy, suggesting that therapeutic re-challenge may have some benefit. Colorectal cancers (CRCs) evolve by a reiterative process of genetic diversification and clonal evolution. The molecular profile of CRC is routinely assessed in surgical or bioptic samples 1 . Genotyping of CRC tissue has inherent limitations; a tissue sample represents a single snapshot in time, and it is subjected to spatial selection bias owing to tumor heterogeneity. Repeated tissue samples are difficult to obtain and cannot be used for dynamic monitoring of disease progression and response to therapy. We exploited circulating tumor DNA (ctDNA) to genotype colorectal tumors and track clonal evolution during treatment with the epidermal growth factor receptor (EGFR)-specific antibodies cetuximab or panitumumab. We identified alterations in ctDNA of patients with primary or acquired resistance to EGFR blockade in the following genes: KRAS , NRAS , MET , ERBB2 , FLT3 , EGFR and MAP2K1. Mutated KRAS clones, which emerge in blood during EGFR blockade, decline upon withdrawal of EGFR-specific antibodies, indicating that clonal evolution continues beyond clinical progression. Pharmacogenomic analysis of CRC cells that had acquired resistance to cetuximab reveals that upon antibody withdrawal KRAS clones decay, whereas the population regains drug sensitivity. ctDNA profiles of individuals who benefit from multiple challenges with anti-EGFR antibodies exhibit pulsatile levels of mutant KRAS . These results indicate that the CRC genome adapts dynamically to intermittent drug schedules and provide a molecular explanation for the efficacy of rechallenge therapies based on EGFR blockade.